Employing omics to investigate the macrophage response to infection with pathogenic and non-pathogenic mycobacteria - Pietersen, Ray-Dean Donovan (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.